Towards for Analyzing Alternatives of Interaction Design Based on Verbal Decision Analysis of User Experience - Mendes, Marília Soares; Carvalho, Ana Lisse; Furtado, Elizabeth; Pinheiro, Plácido Rogério (International Journal of Interactive Mobile Technologies (iJIM), 2010)
In domains (as digital TV, smart home, and tangible interfaces) that represent a new paradigm of interactivity, the decision of the most appropriate interaction design solution is a challenge. HCI researchers have promoted in their works the validation of design alternative solutions with users before producing the final solution. User experience with technology is a subject that has also gained ground in these works in order to analyze the appropriate solution(s). Following this concept, a study was accomplished under the objective of finding a better interaction solution for an application of mobile TV. Three executable applications of mobile TV prototypes were built. A Verbal Decision Analysis model was applied on the investigations for the favorite characteristics in each prototype based on the userâ??s experience and their intentions of use. This model led a performance of a qualitative analysis which objectified the design of a new prototype.